2010
DOI: 10.1021/jo100966j
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Cycloaddition of Dibenzoxazepinium Ylides to Acetylenes and Fullerene C60. Conformational Behavior of 3-Aryldibenzo[b,f]pyrrolo[1,2-d][1,4]oxazepine Systems

Abstract: Cycloaddition of dibenzoxazepinium ylides to acetylene carboxylates leads to cis-3-aryl-3,13b-dihydrodibenzo[b,f]pyrrolo[1,2-d][1,4]oxazepinecarboxylates, which smoothly dehydrogenate to the corresponding pyrrole derivatives. The o-bromophenyl-substituted pyrrole, in contrast to the pyrroline analogue, demonstrates atropoisomerism. Stereoselective cycloaddition of dibenzoxazepinium ylides to fullerene C(60) gives rise to fulleropyrrolidines with cis-configuration. Restricted Ph group rotation is found in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 34 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Hence, Khlebnikov [82] reported the generation of azomethine ylides from aziridine 127 to react it with DMDA (dimethyl acetylenedicarboxylate) or even fullerene (Scheme 33). In the latter case, as fullerene is a poor partner in cycloaddition reactions, the authors found it advantageous to perform the synthesis under microwave irradiation.…”
Section: Ring Expansions Of Nonactivated Aziridines and Azetidinesmentioning
confidence: 99%
“…Hence, Khlebnikov [82] reported the generation of azomethine ylides from aziridine 127 to react it with DMDA (dimethyl acetylenedicarboxylate) or even fullerene (Scheme 33). In the latter case, as fullerene is a poor partner in cycloaddition reactions, the authors found it advantageous to perform the synthesis under microwave irradiation.…”
Section: Ring Expansions Of Nonactivated Aziridines and Azetidinesmentioning
confidence: 99%
“…The stereoselective reaction makes it possible to obtain fulleropyrrolidines 30 with yields of up to 56% both by convection heating and by microwave irradiation [16,17]. The heating of aziridines 26a,b with dimethyl acetylenedicarboxylate (DMAD) in toluene leads to the stereoselective formation of high yields of pyrrolines 31a,b, which are dehydrogenated to the corresponding pyrroles 32a,b under mild conditions [16,17]. The azomethine ylide generated from the aziridine 33 reacts stereoselectively with methyl propiolate, tetrolate, and phenylpropiolate with the formation of a mixture of regioisomeric adducts 34a-c and 35a-c with yields of 73-92% [17].…”
Section: %mentioning
confidence: 99%
“…Oxidation of the aldehydes 68 with I 2 in aqueous ammonia gave the intermediate nitriles, which underwent 1,3-dipolar cycloadditions with sodium azide to afford 5-aryltetrazoles (69) in 70-83% overall yields. In a similar way, benzyl alcohol (70a), N-Cbz-prolinol (70b), and a tyrosine-derived primary alcohol (70c) were converted into 1,2,3,4-tetrazoles (71) (76) and azides in ILs derived from alkylimidazoles (Scheme 17.9) [33]. The temperature was first optimized to achieve complete conversion.…”
Section: Cycloadditions Of Azidesmentioning
confidence: 99%
“…by the addition of a second ylide to the addendum on the nanotube surface to afford an indolizine (174) (Scheme 17.26).More recently, Khlebnikov et al[71] developed a versatile approach for the stereoselective cycloaddition of dibenzoxazepinium ylides (176) to fullerene C 60 . Reactions were carried out either in boiling toluene or in o-dichlorobenzene at 100 • C, and also in toluene or chlorobenzene under MW irradiation.…”
mentioning
confidence: 99%